The Meaning Construction Of Teaching Tools As Communication Technique In Training For Adult Learning - Istanto, Dedy; Maella, Nur’annafi Farni Syam; Harliantara, Harliantara (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Training for adults requires a different and more interactive approach compared to training for children or young people. This research aims to identify the importance role of teaching tools in improving the effectiveness and comfort-feel of the learning process for adult trainees. The method used in the research was descriptive analysis which describes the results of the identification of teaching tools as one of the nonverbal communication techniques. The data analysis was conducted by qualitative analysis by utilizing the results found during the training and by using the results of interviews with participants. The use of Post-it notes was proved to be useful in accommodating participants' ideas and thus making nonverbal communication became more effective. Posters were useful in improving the delivery of information visually and concisely, making it easier for participants to remember and to understand the information conveyed. The meta plan made it easier to convey ideas and thoughts visually, while the design of the room in accordance with the training theme could also increase the motivation, enthusiasm, and build a positive impression. The results showed that the use of training tools helped adults learner to accommodate, to organize, and to communicate ideas more effectively, improving engagement, creativity, memory, and interaction among participants. By understanding and optimizing nonverbal communication, trainers or facilitators can maximize adult learning. Therefore, the trainer or facilitator can unlock the learning potential of adults and put them on the path to success.